Implementation and evaluation of a novel orientation manual for the emergency medicine clerkship and elective rotation - Terry, Sydney; Feldman-Kiss, Damian; McInnes, Gord (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Implication StatementThe Kelowna General Hospital (KGH) Emergency Medicine (EM) Orientation Manual (OM) is a 28-page, mobile-friendly resource designed for medical students to use on- and off-shift. It contains all the academic, clinical, and logistical information needed for the KGH EM rotation, minimizing extrinsic cognitive load while equipping junior learners with tools to enhance learning and performance. The OM is adaptable by modifying the site-specific information while preserving the EM educational content. Future directions include further evaluation of the manual and replication at other University of British Columbia medical school sites, as the curriculum is the same across the province.